Dunking the data center - Cutler, Ben; Fowers, Spencer (IEEE Spectrum, 2017)
When Sean James, who works on data-center technology for Microsoft, suggested that the company put server farms entirely underwater, his colleagues were a bit dubious. But for James, who had earlier served on board a submarine for the U.S. Navy, submerging whole data centers beneath the waves made perfect sense. This tactic, he argued, would not only limit the cost of cooling the machines-an enormous expense for many data-center operators-but it could also reduce construction costs, make it easier to power these facilities with renewable energy, and even improve their performance.